Third World Alternatives for Building Post-capitalist Worlds. (December 2016) - Barkin, David; Lemus, Blanca
In the context of great diversity and profound social inequalities, environmental injustice prevails. Conflicts between institutions promoting economic development (i.e., growth) and ecologists and civil society are rampant. This paper introduces alternatives emerging from groups, whose organizations are shaped by different cosmologies, products of their multiple ethnic origins, and by the profound philosophic and epistemological debates among social movements proposing different strategies for achieving progress, improving well-being and conserving ecosystems.